W. Oliver Martin, Metaphysics and Ideology. [Reseña del libro Metaphysics and Ideology, de W. Oliver Martin] - Scannone, Juan Carlos (Ciencia y Fe, 2022)
Reseña del libro Metaphysics and Ideology, de W. Oliver Martin.